Pyroptosis: A Novel Intervention Target in the Progression of Osteoarthritis - Chang X; Kang Y; Yang Y; Chen Y; Shen Y; Jiang C; Shen Y (Dove Medical Press, 2022)
Xingyu Chang,1,* Yuchen Kang,2,* Yuxuan Yang,1,* Yajie Chen,1 Yanyu Shen,1 Chenjun Jiang,1 Yi Shen3 1The First Clinical Medical College, Lanzhou University, Lanzhou, People's Republic of China; 2The Second Clinical Medical College, Lanzhou University, Lanzhou, People's Republic of China; 3Department of Orthopaedics, The Second Xiangya Hospital of Central South University, Changsha, People's Republic of China*These authors contributed equally to this workCorrespondence: Yi Shen, Department of Orthopaedics, The Second Xiangya Hospital of Central South University, Changsha, People's Republic of China, Tel +86-13517490910, Email shenyiak487@163.comAbstract: Osteoarthritis (OA) is one of the most common chronic joint diseases and is gradually becoming the main cause of disability and joint pain in the elderly worldwide. Pyroptosis is a regulated programmed cell death triggered by inflammasomes. It leads to cell swelling, lysis, and bioactive molecule secretion. Studies found that the damaged chondrocytes in OA joints had morphological characteristics of pyroptosis, and the cytokines associated with pyroptosis in synovial fluid increased, indicating that pyroptosis may have certain impacts on the pathological progression of OA. This review briefly summarizes the molecular mechanisms of pyroptosis and the epidemiology and pathogenesis of OA. Furthermore, we discussed the role of pyroptosis in articular cartilage and synovium during OA and reviewed the progress of pyroptosis-related molecules in the targeted therapy of OA joints, hoping to provide feasible directions for the diversified treatment of OA.Keywords: pyroptosis, osteoarthritis, articular cartilage, synovium, NLRP3 inflammasome, GSDMD